Desarrollo de una aplicación web y móvil para la gestión y ventas de insumos florícolas para los clientes de la empresa Flor Insumos S.A.S de la ciudad de Cayambe, mediante el uso de prácticas ágiles. - Anchapaxi Gordon, Elvis Fabricio (2023)
The current project involves a web and mobile application development aimed to management and sale of floricultural inputs for clients at "Flor Insumos S.A.S." company The implementation of this technological application gains fundamental importance enabling dissemination and commercialization of floricultural inputs through Internet. This initiative seeks to enhance information accessibility, characterized by offering reliability, integrity, and over all, products availability. SCRUM methodology was employed to guide software development, chosen for its adaptability to projects specificities. One of the most highlighted aspects among these requirements is the management of floricultural input sales by clients. By the set of used tools for project execution, MySQL was, employed as database management system. Likewise, PHP with Codeigniter framework was adopted, providing necessary functionalities to develop modern applications securely and efficiently. For mobile version, Android Studio was chosen, and agile practices were followed in the development process. The implementation of this system proved to be an effective response to previously manual processes, characterized by their extensive duration. Thanks to the incorporation of this management solution, search for information was streamlined, a more precise control over data was established, and data integrity was maintained